1955
DOI: 10.1063/1.1722162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attenuating Materials on Detonation Induction Distances in Gases

Abstract: The effectiveness of acoustic absorbing wall materials in delaying the onset of detonation in gases is explored. Experiments are reported for stoichiometric H2–O2 mixtures in two-inch diameter cylindrical tubes. The results show that the detonation induction distance may be increased by as much as a factor of two by making the walls of the tube of porous sintered bronze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For example, in a porous walled material, Evans et al (1955) found that the onset of detonation was delayed. In compliant thin plastic-walled tubes Murray (1985) observed that there is no progressive amplification of the transverse waves as a result of the reflection from the walls.…”
Section: Introductionmentioning
confidence: 97%
“…For example, in a porous walled material, Evans et al (1955) found that the onset of detonation was delayed. In compliant thin plastic-walled tubes Murray (1985) observed that there is no progressive amplification of the transverse waves as a result of the reflection from the walls.…”
Section: Introductionmentioning
confidence: 97%
“…Perhaps the earliest experiment on detonation and shock wave absorption was reported by Evans et al (1955), who studied the transition to detonation in a tube lined with an acoustic damping material (porous sintered bronze) and found that the transition was delayed or even prevented. Later it was recognized that transverse waves are essential to the propagation of detonation waves and Strehlow (1969), Fowles (1984) and Edwards (1969) are amongst many who contributed to our present understanding of the microscopic nature of detonation strucCorrespondence to : Changming Guo (e-mail: cmguo@ustc.edu.cn) ture and the significance of the detonation 'cell'.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most convincing experiment that indicates their important role is the work of Evans et al (1955). Perhaps the most convincing experiment that indicates their important role is the work of Evans et al (1955).…”
Section: Introductionmentioning
confidence: 99%